Respuestas

2013-11-18T11:03:36+01:00

Vamos a determinar la razón
En una PA
   an = a1 + (n - 1).r
    an = 17/5                          17/5 = 2/5 + (6 - 1).r
    a1 = 2/5                             r = (17/5 - 2/5)/5
      n = 6                                  = (15/5)/3
                                              r = 3/5
Cada término es el anterior mas la razón
PA =
2/5, 5/5, 8/5, 11/5, 14/5, 17/5

a1 = 11
  r = - 2
 S = - 28
 n = ??
                  S = (a1 + an).n/2
- 28 = (11 + an).n/2
- 56/n = 11 + an
an = - 56/n - 11               (1)
an = a1 + (n - 1).r
an = 11 + (n - 1)(- 2)       (2)
(1) = (2)
- 56/n - 11 = 11 - 2n + 2
- 56/n + 2n - 24 = 0
   todo x n
- 56 + 2n^2 - 24n = 0
  n^2 - 12n - 28 = 0
  Factorizando
  (n - 14)(n + 2) = 0
        n - 14 = 0              n1 = 14
        n + 2 = 0               n2 = - 2
n debe ser positivo
Número de términos = 14